(untitled) (Ozone Therapy Global Journal, 2011)
This pilot study describes the clinical effects of Adjunctive Hyperbaric Oxygen Therapy (HBOT) and Ozone Therapy in the treatment of chronic ulcers most of which did not respond to standard wound care and conventional methods of therapy and the patients were threatened by amputation. HBO and Ozone Therapy increased the healing rate of these ulcers, and avoided amputation. Adjuvant HBO and Ozone Therapy showed effectiv e adjun ctive the rapy and we re commend a Randomized Controlle d Trial to prove that effect.